2007
DOI: 10.3121/cmr.2007.741
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Luteinizing Hormone to Alzheimer Disease Pathogenesis

Abstract: Al zheimer Disease (AD) is the most prevalent neurodegenerative disease affecting more than 15 million people worldwide 1 and is characterized by selective neuronal degeneration resulting in progressive memory loss. 2 AD attacks several different regions of the brain including the cerebral cortex which is involved in conscious thought and language, the basal forebrain which is important in memory and learning, and the hippocampus which is essential to memory storage. Clinical manifestations of AD are varied bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 85 publications
1
26
0
2
Order By: Relevance
“…In the case of the gender specificity of hemolytic E. coli-mediated colonic tumorigenesis, the genetic factor is ruled out because our in vitro data showed that hemolytic E. coli had cytotoxic and tumorigenic effects on cell lines that are derived from men. It is therefore speculated that the gender specificity observed in this study might be associated with immunological, hormonal, or behavioral factors that have been linked to gender difference in disease development (40)(41)(42)(43). Our animal experiments showed that hemolytic E. coli significantly induced colonic tumorigenesis in female mice but failed to do so in male mice, confirming the gender specificity of hemolytic E. coli-mediated colonic tumorigenesis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the case of the gender specificity of hemolytic E. coli-mediated colonic tumorigenesis, the genetic factor is ruled out because our in vitro data showed that hemolytic E. coli had cytotoxic and tumorigenic effects on cell lines that are derived from men. It is therefore speculated that the gender specificity observed in this study might be associated with immunological, hormonal, or behavioral factors that have been linked to gender difference in disease development (40)(41)(42)(43). Our animal experiments showed that hemolytic E. coli significantly induced colonic tumorigenesis in female mice but failed to do so in male mice, confirming the gender specificity of hemolytic E. coli-mediated colonic tumorigenesis.…”
Section: Discussionsupporting
confidence: 59%
“…It is beyond the scope of this study but warrants further investigation why females are more vulnerable to colorectal cancer carcinogenesis mediated by hemolytic type I E. coli. Gender-dependent differences have been known to exist in the etiology and pathogenesis of a long list of diseases such as heart failure (39), viral infections (40), and Alzheimer disease (41). Mechanisms underlying the gender difference remain poorly understood and may involve complex processes.…”
Section: Discussionmentioning
confidence: 99%
“…This observation in conjunction with the animal data 19 showing that the use of a LHRH agonist to markedly lower serum LH levels led to improved hippocampally related cognitive performance provides the basis on which to assess whether reducing serum levels of LH may be of therapeutic value in people with AD. Moreover, additional evidence 20-23 supports the possible therapeutic role for LHRH agonists in slowing and/or eliminating the development of AD and its associated cognitive decline which leads to death.…”
Section: Discussionmentioning
confidence: 75%
“…Currently, phase II clinical trials are underway testing leuprolide acetate as a possible therapy for Alzheimer's disease and, interestingly, women undergoing treatment showed stabilization of cognitive decline, whereas men were not as responsive to the treatment [66 ]. This may be due to the fact that, unlike menopause, andropause is a gradual process, and leuprolide acetate would deplete remaining circulating sex hormones in men but not in women, leading to detrimental cognitive effects.…”
Section: Gonadotrophins and Alzheimer's Diseasementioning
confidence: 86%